Math, asked by prashantkhare2008, 3 months ago

2x + 3 / 3 - 3x-2 / 4 = 1​

Answers

Answered by shahmadhu200
1

Step-by-step explanation:

 \frac{2x + 3}{3}  -   \frac{3x - 2}{4}  = 1 \\  \\  \frac{8x + 12 - 9x + 6}{12}  = 1 \\  \\  \frac{x + 18}{12}  = 1 \\  \\ x + 18 = 1 \times 12 \\  \\ x + 18 = 12 \\  \\ x = 12 - 18 \\  \\ x =  - 6

I hope it helps you

Answered by natarajan17041975
1

Step-by-step explanation:

2x+1-3x-0.5=1

1= 0.5+x

1-0.5= 0.5= x

substitute x in the above

1+1-1.5-0.5= 1

Similar questions